Inappropriate feeding practices as a risk factor for severe acute malnutrition in children aged between one month to five years: a case control study - H., Deepak D. (International Journal of Contemporary Pediatrics, 2022)
Background: In developing country like India, inappropriate feeding practices like lack of exclusive breastfeeding, early or late introduction of complimentary diet, lack of direct breastfeeding, prelacteal feed, bottle feeding are the major risk factors for development of severe acute malnutrition in children aged between one month to five years. Methods: It was a case control study, 109 children aged between one month to five years with severe acute malnutrition (SAM) who fulfilled the WHO criteria for SAM admitted to KIMS Hubli were taken as cases and 109 children aged between one month to five years without SAM admitted to KIMS Hubli were taken as control, the data gathering tool was questionnaire of children and mother. Data were entered and analysed using SPSS software version 11. Proportions were compared using Chi square (χ2) test of significance, categorical variables were assessed using χ2. Odds ratio (OR) and 95% confidence interval (CI) were calculated. To estimate the independent effect of the factors that were significantly associated with SAM and to control the confounding effect they may have on each other, logistic regression analysis was done. In all the above test the p value of less than 0.05 was accepted as indicating statistical significance. Results: In the study lack of EBF (exclusive breastfeeding), DBF (direct breastfeeding), h/o prelacteal feeds, h/o bottle feed and late initiation of complimentary diet >6 months were significantly associated with SAM (p value less than 0.05). Conclusions: The findings of this study clearly establishes the association of SAM with inappropriate infant feeding practices prevailing in our country.